Revisiting the morphology of pelvicalyceal system in human cadaveric kidneys with a systematic review of literature - Kusum Rajendra Gandhi; Sushama Chavan (Asian Journal of Urology)
Objective: Renal collecting system macroscopically consists of minor calyx, major calyx, renal pelvis and ureter. Stone in renal collecting system is a common presentation in everyday urological practice. The prevalence of renal calculi ranges from 4% to 20% in different geographical distribution. Anatomical variation in renal collecting system plays a significant role in formation of calculi in its parts. The large extra renal pelvis leads to stagnation of urine for longer durations and formation of stones. The stone free rate after percutaneous nephrolithotomy and extra corporeal shock wave lithotomy is significantly related to anatomical factors, particularly the type of renal pelvis and dimensions (length and width) of lower infundibulum. Previous authors described the morphology of pelvicalyceal system in a highly variable manner and the available anatomical description of pelvicalyceal system is contradictory and incomplete. Hence an attempt has been made to provide the precise anatomy of pelvicalyceal system in adult human kidneys. Methods: We studied 196 formalin embalmed kidneys to note the number of infundibulum, major and minor calyces. The location and shape of pelvis were also studied. Results: The intra-renal pelvis was narrow and had funnel shaped appearance in 95 of total 196 (48.5%) specimens, and the extra-renal pelvis was dilated as balloon shaped in 43 of 196 (21.9%) specimens. In 41 (20.9%) specimens, the renal pelvis was having partially intra- and extra-renal in location. Bilateral symmetry was found in only 27.1% of 196 renal collecting systems. The length of lower infundibulum was more than 22 mm in 19 (9.7%) of 196 cases which directly affects the stone clearance rate during open and endoscopic surgeries on pelvicalyceal system. Conclusion: This study provides the accurate morphological details of the shape and dimensions of renal pelvicalyceal system to help the urologists and nephrologists. Keywords: Renal pelvis, Morphology, Pelvicalyceal system, Urologists, Renal calculi, Intra-renal pelvis